Synthesis of novel hard/soft ferrite composites particles with improved magnetic properties and exchange coupling - Faezeh Tavakolinia; Mohammad Yousefi; Seyyed Salman Seyyed Afghahi; Saeid Baghshahi; Susan Samadi (Processing and Application of Ceramics, 2018)
SrFe12O19/Zn0.4Co0.2Ni0.4Fe2O4 hard/soft ferrite composite particles with 20, 40, 60 and 80 wt.% of soft phase were prepared by one-pot sol-gel auto-combustion and physical mixing methods. Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), field emission scanning electron microscope (FESEM) and vibrating sample magnetometer (VSM) were used to characterize the structural and magnetic properties of the samples. XRD spectrum revealed the formation of mixed ferrite phases in the composite particles. The hysteresis loops of the samples showed the presence of exchange coupling between the hard and soft ferrites. The composite particles with 20 and 60 wt.% of the soft phase demonstrated the highest Mr/Ms ratio, i.e. 0.29 and 0.28, respectively. In addition, the highest Ms, Mr and Hc were achieved in the composite particles with 40, 60 and 20 wt.% of the soft phase, respectively. Compared to the physical mixing method (PM), the composite particles prepared by the sol-gel auto-combustion method (OP) demonstrated better magnetic properties. The exchange coupling interaction between the hard and soft ferrite phases was similar in both methods. These composite particles exhibited magnetically single phase behaviour, however, the saturation magnetization was lower in the physical mixing pared to that of the one-pot method.